Evolution of charged grains in harmonic force field. Issue 9 (12th May 2020) - Wang, Youmei; Guan, Miao; Yu, Mingyang
Abstract: Evolution of the spatial structure of the massive charged grains in the presence of weak linearly space‐dependent external force in a dusty plasma is studied using molecular dynamics simulation. The interaction among the dust grains in the background electron‐ion plasma is described by a modified Yukawa interaction potential that includes both repulsive and attractive ranges. Evolution of the initially homogeneously distributed dust grains is followed until a quasi‐stationary state is reached. Even though the external force is radially highly asymmetric, the final configuration of the charged grains can be a circular crystal. Still driven by the external force, the grains in the crystal execute synchronized oscillations in the direction of the force. The time needed to reach the quasi‐stationary state decreases with increase of the strength of the external force. Abstract : Directed coherent grain oscillations in circular dust crystal formed in the presence of weak linearly space‐dependent external force in the same direction. The time needed to form the crystal, but not the crystal size, depends on the force strength. The grain oscillation period scales as the inverse square root of the latter.